2019
DOI: 10.3390/vetsci6030066
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Bovine Leukemia Virus RNA in Blood Samples of Naturally Infected Dairy Cattle

Abstract: The viral expression in vivo, in bovine leukemia virus (BLV)-infected cattle, is considered to be restricted to extremely low levels, and the mitosis of infected B lymphocytes is regarded as the main mode of virus persistence within the infected host. In this study, the presence of BLV RNA in whole blood from seven asymptomatic cows naturally infected with BLV during one year, including a complete milking cycle and two delivery time points, was investigated by nested-PCR using the oligonucleotides complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…The differential expression (measured in ex vivo cultivated PBMC) has been attributed to polymorphisms in the TNF gene regulatory region (Konnai et al, 2006a;Lendez et al, 2015). The BLV transcription is mostly silent during nonacute stages of infection (Gillet et al, 2013), although some spontaneous reactivation could be observed in vivo (Alvarez et al, 2019;Jaworski et al, 2019). On the other hand, BLV transcription is easily reactivated by ex vivo whole-blood cultivation from infected cows (Tajima and Aida, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression (measured in ex vivo cultivated PBMC) has been attributed to polymorphisms in the TNF gene regulatory region (Konnai et al, 2006a;Lendez et al, 2015). The BLV transcription is mostly silent during nonacute stages of infection (Gillet et al, 2013), although some spontaneous reactivation could be observed in vivo (Alvarez et al, 2019;Jaworski et al, 2019). On the other hand, BLV transcription is easily reactivated by ex vivo whole-blood cultivation from infected cows (Tajima and Aida, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Зараз у світі для прижиттєвої ідентифікації BLV-позитивних тварин серед поголів'я великої рогатої худоби використовують реакцію імунодифузії (РІД), або AGID (agar gel immunodiffusion), імуноферментний аналіз (ІФА), або ELISA (enzyme-linked immunosorbent assay) та молекулярногенетичний (ПЛР), або PCR (polymerase chain reaction) [18][19][20][21].…”
Section: вступunclassified
“…Із 27-ми районів і населених пунктів благополучними виявлено 10. До таких віднесено Великобагачанський, Котелевський, Лохвицький, Лубенський, Миргородський, Семенівський, Хорольський, Шишацький райони та міста Горішні Плавні й Полтава.Варто зазначити, що найбільшу кількість (58,44 %) великої рогатої худоби, яка позитивно реагує, виявлено в умовах 4-х районів області -Глобинському(21), Гребінківському (28), Козельщинському (30) та Оржицькому (56). На решту районів області припало 41,56 % кількість худоби з таким ж показниками, при цьому її кількість у розрізі районів коливалася у межах від 1 до 16 голів.…”
unclassified
“…Techniques based on DNA amplification methods allow direct detection of proviral DNA or viral RNA and they are "gold standard". PCR is the primary method to detect the latent stage of EBL, to verify the doubtful results of serological tests, to identify infected calves up to 6 months and also to distinguish lymphoma viral etiology and neoplasms [13][14][15][16][17][18]. Nested PCR is recommended to use as more sensitive among other variants of PCR according to the OIE protocol for EBL diagnostic.…”
mentioning
confidence: 99%